Potret Keterampilan Metakognitif Problem Solving dalam Level Penalaran Kontroversial Siswa - Apriana Swastika; Eka Resti Wulan; Dewi Hamidah (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2022)
The purpose of this study is to describe the metacognitive problem-solving skills of class X SMA Negeri 1 Kediri students at the level of initial controversial reasoning, exploration, and clarification, when solving irrational inequality problems. This research is descriptive research with a qualitative approach. Data collection techniques used controversial problem tests, problem-solving tests, think-aloud methods, and task-based semi-structured interviews. The data analysis technique used was qualitative data analysis with steps of data reduction, data presentation, and conclusion. The validity of the data used triangulation techniques and member checks. The results show that students' metacognitive problem-solving skills at the initial controversial reasoning level can meet the three indicators of metacognitive activity at the stage of understanding problems and determining the problem-solving strategy plan. Students' metacognitive problem-solving skills at the level of exploration can fulfill the three indicators of metacognitive activity at the stage of understanding problems, determining the problem-solving strategy plans, and completing problem-solving strategies. Students' metacognitive problem-solving skills at the level of clarification can meet the three indicators of metacognitive activity at the stage of understanding the problem, determining the problem-solving strategy plan, completing the problem-solving strategy, and looking back.